Aquaculture extension impacts in Bangladesh a case study from Kapasia, Gazipur - Thompson, Paul M.; Sultana, Parvin; Firoz Khan, A.K.M. (Penang, Malaysia The WorldFish Center, 2005)
WorldFish Center Technical Report, 63
Keywords: Fish culture; Aquaculture